The Effect of A High-Fat Diet on Lipid Profile Levels (LDL Cholesterol, HDL Cholesterol, Triglycerides, and Total Cholesterol) in Male Rattus Novergicus with Obese - Ibrahim Ibrahim; Eti Yerizel; Endrinaldi Endrinaldi; Gusti Revilla (Indonesian Journal of Global Health Research, 2025)
Obesity is a complex disease that has a significant impact on public health and its prevalence is increasing worldwide. Obesity causes lipid accumulation in adipose tissue. The purpose of this study was to determine the effect of a high-fat diet on lipid profiles in male white rats. This study used a true experimental study on male white rats with a post-test control-only group design. The group division in this study was divided into two groups, consisting of a negative control group (K1) of 5 rats and a HFD group (K2) of 20 rats. This study was conducted from October 2024 to April 2025 at the Biomedical and Biochemistry Laboratory, Faculty of Medicine, Andalas University. The population in this study were male white rats of the Rattus norvegicus strain wistar obtained from the Biomedical Laboratory, Faculty of Medicine, Andalas University. The sampling technique in this study used purposive sampling. The number of samples used in this study was 25 rats with a minimum reserve of 10%. The results of the study with the average values of LDL cholesterol, HDL cholesterol, Total cholesterol, and TG levels in the K1 group were 45.72, 62.28, 67.66, and 107.60 mg/dL, respectively, while in the K2 group they were 61.62, 43.14, 83.17, and 167.20 mg/dL, respectively. Based on the results of the independent T test, the significance of the two groups was 0.001, 0.001, 0.001, and 0.005, respectively, which means there was a significant or real difference in the average levels of LDL, HDL, total cholesterol, and triglycerides in the K1 and K2 groups.